Growth, Dry Matter Production and Yield Characteristics of Greater Yam+Maize Intercropping System Under Varied Drip Irrigation and Fertigation Levels - M, Nedunchezhiyan; Pati, Kalidas; Chauhan, Chauhan; R, Arutselvan; K, Laxminarayana; G, Byju; S.S., Veena (JOURNAL OF ROOT CROPS, 2022)
Field experiments were conducted during 2015-16 and 2016-17 to study the influence of drip irrigation and fertigation on growth, dry matter production and yield characteristics of greater yam+maize intercropping system. The treatments comprised of a combination of three levels of drip irrigation [I1- at 80% of cumulative pan evaporation (CPE) during 1-270 days after planting (DAP), I2-at 100% of CPE during 1-90 DAP + at 80% of CPE during 91-270 DAP and I3-at 100% of CPE during 1-270 DAP] in main plots and four levels of fertigation (F1-N-P2O5-K2O @ 100-90-100 kg ha-1, F2-N-P2O5-K2O @ 120-90-120 kg ha-1, F3-N-P2O5-K2O @ 140-90-140 kg ha-1 and F4-N-P2O5-K2O @ 160-90-160 kg ha-1) in sub plots along with a control (surface irrigation treatment at 100% of CPE; soil application of N-P2O5-K2O @ 120-90-120 kg ha-1). Drip irrigation at I3 resulted in higher maize and greater yam growth and dry matter production. The treatment F4 resulted in greater yam and maize growth and dry matter production. The interaction effects revealed that highest maize yield was recorded in I3F4 whereas the treatment I2F4 resulted in higher greater yam yield. However, maize and greater yam yield in the treatment I2F3 was found statistically at par with I3F4 in maize and I2F4 in greater yam. The treatments control (surface irrigation at 100% of CPE with soil application of N-P2O5-K2O @ 120-90-120 kg ha-1) and I1F2 [drip irrigation at I1 with fertigation of same level of nutrients (F2)] resulted in same level of maize and greater yam yields. Thus, drip irrigation saved 0.684-0.710 million litre (17.9-25.9%) of water per ha. Same level of maize and greater yam yields with the treatments control and I2F1/I3F1 also indicated a saving of nutrients N-K2O @ 20-20 kg ha-1 (20%) under drip fertigation. Considering water and fertilizer use efficiency and response, the treatment I2F3 (irrigation at 100% of CPE during 1-90 DAP + at 80% of CPE during 91-270 DAP with N-P2O5-K2O @ 140-90-140 kg ha-1) is recommended for greater yam+maize intercropping system